Inflation and DER Fluctuations: The Underpricing Phenomenon - Yandes, Jufri (Almana : Jurnal Manajemen dan Bisnis, 2024)
Capital markets reflect economic progress, with IPO and underpricing illustrating market and investor efficiency. This study aims to see how inflation and DER variables impact the underpricing value during the IPO years from 2021 to 2022. For this study, a purposive sampling method was applied to sort out a sample of 75 issuers during the period with respect to certain criteria. The hypotheses of this study were tested using multiple linear regression analysis using the EViews program. The main data comes from the prospectus of issuers listed on the Indonesia Stock Exchange (IDX). The inflation variable may or may not have a significant impact on the underpricing phenomenon. Where also the coefficient results are negative on the inflation value from 2021 to 2022, meaning that the greater the increase in the inflation variable, the value of stock under-pricing will decrease. The study results also contradict the results of the inflation T-test, explaining that the DER variable may or may not have a significant effect on the underpricing of IPO shares, but from 2021 to 2022 based on the F test, the underpricing of IPO shares is influenced by the DER and inflation variables simultaneously.